The influence of differente speeds on backpacker's gait kinectics - Castro, Marcelo Peduzzi (2011)
This study analyzed the influence of different speeds on ground reaction force’s (GRF), impulses and mean vertical force during gait of people submitted to occasional overload (backpack). A force plate was used to record the GRF data of 60 young adult subjects walking in two different cadences: 69 steps/min (slow gait) and 120 steps/min (fast gait). During the slow gait, the impact and propulsive impulses of vertical GRF, propulsive impulse of anterior-posterior GRF, impulse of medial-lateral GRF and duration of stance phase were larger than during the fast gait; the mean vertical force was the only variable that showed larger values during fast gait. Therefore, slow gait may present a larger possibility of blister development and gait unbalance, while the fast gait, even presenting a small impulse, seems to be more harmful to the musculoskeletal system.